A High Efficiency Nonfullerene Organic Solar Cell with Optimized Crystalline Organizations. Issue 5 (7th December 2015) - Kwon, Oh Kyu; Uddin, Mohammad Afsar; Park, Jung‐Hwa; Park, Sang Kyu; Nguyen, Thanh Luan; Woo, Han Young; Park, Soo Young
Abstract : A well‐organized donor –acceptor crystalline structure is examined for high performance nonfullerene solar cells. By thermal annealing, nanoscale structures of both donor and acceptor domains are successfully modulated, followed by significant changes in the resulting photovoltaic characteristics. When annealed at 90 °C, a maximum power conversion efficiency of 7.64% with a remarkable open‐circuit voltage of 1.03 V is obtained.